2009
DOI: 10.1038/ni.1744
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage colony-stimulating factor induces the proliferation and survival of macrophages via a pathway involving DAP12 and β-catenin

Abstract: Macrophage colony stimulating factor (MCSF) influences proliferation and survival of mononuclear phagocytes through the CSF-1 receptor. The DAP12 adaptor protein, which transduces signals emanating from various myeloid receptors, is critical for mononuclear phagocyte function. DAP12-mutant mice and humans show defects in osteoclasts and microglia and exhibit brain and bone abnormalities. Here, we demonstrated that DAP12 deficiency impairs MCSF-induced macrophage proliferation and survival in vitro. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
256
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(273 citation statements)
references
References 51 publications
17
256
0
Order By: Relevance
“…One possibility is that I-mfa suppresses the survival and/or proliferation of early osteoclast progenitors in response to M-CSF. Interestingly, M-CSF signaling is essential for the proliferation and survival of these progenitors through the up-regulation of ␤-catenin mediated by the action of the Ca 2ϩ -sensitive Pyk2 tyrosine kinase (3). Therefore, we could envision a positive feedback loop whereby accumulated ␤-catenin could compete with TRPC1 for binding to I-mfa, relieving the I-mfa-mediated suppression of TRPC1 activity, thus allowing for Ca 2ϩ influx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that I-mfa suppresses the survival and/or proliferation of early osteoclast progenitors in response to M-CSF. Interestingly, M-CSF signaling is essential for the proliferation and survival of these progenitors through the up-regulation of ␤-catenin mediated by the action of the Ca 2ϩ -sensitive Pyk2 tyrosine kinase (3). Therefore, we could envision a positive feedback loop whereby accumulated ␤-catenin could compete with TRPC1 for binding to I-mfa, relieving the I-mfa-mediated suppression of TRPC1 activity, thus allowing for Ca 2ϩ influx.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, these precursors differentiate into multinucleated osteoclasts in a multistep process dependent on M-CSF and receptor activator of nuclear factor-B ligand (RANKL) (2). Both of these factors act through Ca 2ϩ signaling to induce downstream regulators of osteoclastogenesis such as nuclear factor of activated T cells c1 (NFATc1), NF-B, c-fos, ␤-catenin, and others (3,4). However, the molecular identity of the Ca 2ϩ channels essential for osteoclastogenesis is only recently starting to emerge.…”
Section: Camentioning
confidence: 99%
“…The cytoplasmic domain of DAP12 contains immunoreceptor tyrosine-based activation motifs (ITAMs), which become phosphorylated in response to CSF-1R activation, recruiting and activating the cytosolic tyrosine kinase Syk, which activates the Pyk2 tyrosine kinase that phosphorylates b-catenin, triggering its nuclear translocation and activation of cell-cycle genes. The response is enhanced by DAP12-independent CSF-1R inhibition of b-catenin degradation (Otero et al 2009). DAP12 deficiency leads to impaired CSF-1R-mediated proliferation and survival, but does not affect differentiation (Nataf et al 2005;Otero et al 2009).…”
Section: Er Stanley and V Chitumentioning
confidence: 99%
“…The response is enhanced by DAP12-independent CSF-1R inhibition of b-catenin degradation (Otero et al 2009). DAP12 deficiency leads to impaired CSF-1R-mediated proliferation and survival, but does not affect differentiation (Nataf et al 2005;Otero et al 2009). …”
Section: Er Stanley and V Chitumentioning
confidence: 99%
“…It has been shown that Pyk, a tyrosine kinase, phosphorylates β-catenin at tyrosine residues [195,196]. This phosphorylation is associated with decreased attachment to Ecadherin and increased stability and nuclear translocation of β-catenin [197].…”
Section: Pyk2 Play a Role In Nuclear Accumulation Of β-Catenin In Nodmentioning
confidence: 99%